Incidente de negocios DISTRIBUIDOR CONQUISTADO, VENTA REALIZADA - Solano, David (1996)
This business incident, which lends itself to an eminently qualitative analysis, seeks to illustrate how the marketing mix of a company should be structured, taking into account not only the product to be launched on the market, but also the client portfolio with which account the company. Another aspect to analyze is the decision-making style and its influence on marketing decisions. It is recommended that the solution culminate with the marketing mix proposal that the company must implement and the planning of the actions that must be carried out for this, both inside and outside the company. The analysis of the situation should be taken into account.